2002
DOI: 10.1097/00001756-200208270-00004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and nicotine reduce cell proliferation and enhance apoptosis in dentate gyrus

Abstract: It is generally accepted that alcohol and nicotine affect learning ability and memory functions, especially in adolescents. In the present study, the effects of alcohol and nicotine on cell proliferation and apoptosis in the dentate gyrus of young rats were investigated. The results show that cell proliferation is suppressed by alcohol and nicotine. Furthermore, alcohol and nicotine increase the number of terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL)-positive cells. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
41
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 22 publications
13
41
1
Order By: Relevance
“…This finding supports suggestions by Jang et al [49] that 3 days of nicotine exposure in adolescent male rats induced a 110% increase in active caspase-3 from the dentate gyrus.…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports suggestions by Jang et al [49] that 3 days of nicotine exposure in adolescent male rats induced a 110% increase in active caspase-3 from the dentate gyrus.…”
Section: Discussionsupporting
confidence: 92%
“…Our own work showed that a single, acute dose of alcohol (5 g/kg by gavage) inhibited cell proliferation by around 40% as examined with BrdU labeling. Jang et al (2002b), as mentioned earlier, had also shown a similar decrease with three days of single injections at 4 g/kg (i.p.) and reported that alcohol dose dependently decreases cell proliferation even at a dose of 0.5 g/kg (i.p., once a day for 3 days) in adolescent rats.…”
Section: Alcohol Inhibition Of Adult Neurogenesis: Different Mechanissupporting
confidence: 78%
“…It has been shown previously that in vivo nicotine exposure reduces proliferation in the DG, but not in the SVZ (10,11). In light of these reports, the data obtained here with chronic nicotine administration starting after the proliferation phase suggest that once differentiation has started, the survival of DG cells is no longer affected by nAChR activity.…”
Section: Discussionsupporting
confidence: 61%
“…In vitro activation of the latter by low doses of nicotine has been shown to lead to apoptotic cell death of undifferentiated primary and immortalized progenitor cells from the dentate gyrus (DG), the other main region of neurogenesis in the mature brain (9). In accordance with these results, in vivo chronic nicotine exposure in adult rats was shown to reduce proliferation in the DG (10,11). Interestingly, nicotine exposure had no effect on proliferation in the SVZ, suggesting that nAChRs might not be involved in adult OB neurogenesis.…”
mentioning
confidence: 69%